Influence of Oxygen Substoichiometry on the Dielectric Properties of BaTiO3‐δ Nanoceramics Obtained by Spark Plasma Sintering. (8th April 2013) - Voisin, Christophe; Guillemet‐Fritsch, Sophie; Dufour, Pascal; Tenailleau, Christophe; Han, Hyuksu; Nino, Juan C.
Abstract : Oxygen‐deficient BaTiO3‐δ nanoceramics were prepared by spark plasma sintering. Partially reduced raw nanopowders led to unusual dielectric properties. A short postsintering treatment was performed to reach a high εr /tan δ, which makes them attractive for industrial applications such as low‐frequency capacitors. Surprisingly, our ceramics also remained black even after annealing for 5 days at 850°C in air, indicating the presence of barriers against oxygen diffusion. This exceptional behavior in pure barium titanate was consistent with a core–shell structure made of semiconductive grains and insulating grain boundaries, due to the presence of Ti 3+ /Ti 4+ and oxygen vacancies.